THE GLOBAL COMPETITIVENESS STUDY OF HALAL PHARMACEUTICALS AND COSMETICS INDUSTRY - Ernawati Ernawati (Universitas Muhammadiyah Kendari, 2019)
This research aimed to determine the position of global competitiveness of the halal pharmaceutical and cosmetics industries. The secondary data used data about the state of the global Islamic economy 2014-2017 period from Thomson Reuters Publication. Data analyzed using charts and descriptive statistics. The data were categorized into very low ratings to very high. The results showed that (1) the highest competitiveness in global pharmaceutical and cosmetics industry was the United Arab Emirates (UEA) followed by Malaysia and then Singapore. The high global competitiveness of the UAE is driven by the government role in halal pharmaceuticals and cosmetic regulations, public awareness, and social factors. The indicator of export UEA was also in the high category of competitiveness in the global pharmaceutical and cosmetics industry, even though the value is lower than Singapore; (2) Indonesia has a major advantage in the low of costs of halal pharmaceuticals and cosmetics industry; and (3) the Muslim countries generally still have a very low-level of awareness of halal pharmaceuticals and cosmetics industry